Using the national electronic prescription system to determine the primary non-adherence to medication in the Czech Republic - Bruthans, Jan; Berger, Jiří; Šoltés, Ján; Michálek, Pavel (Frontiers in Pharmacology, 2023)
The primary medication non-adherence occurs when a patient does not collect his or her newly prescribed medication. Various studies give estimates that this occurs between 0.2 percent and 74 percent. Recently, this topic has been researched by analyzing data in national electronic prescription systems. The database of the Czech electronic prescription system was used to obtain the number of all prescriptions issued and collected in 2021 for fifty particular substances (associated with six medication groups). Additionally, a similar query was performed with an additional criterion that the same substance had not been prescribed within the last 365 days. The data were obtained separately in five age categories. The total number of prescriptions analyzed in this study was over 21 million, which represents almost 30 percent of all prescriptions issued in the Czech Republic in 2021. The primary medication non-adherence in the selected substances was 4.56 percent, which negatively correlates (rxy = 0.707) with the age of a patient. There is a higher primary non-adherence in the Psychoanaleptics and Lipid modifying medication groups than in the whole studied sample (p < 0.05). Lipid-modifying medication group and several other particular substances showed a larger difference between primary non-adherence and overall non-adherence, indicating issues in the initiation of these drugs. The results of our study are following earlier studies with similar methodologies from other countries. However, the difference between primary non-adherence and overall non-adherence had not been observed in other studies before. The electronic prescription system proved to be a valuable tool for conducting this type of research.